Evaluation of genetic instability, oxidative stress, and metabolism-related gene polymorphisms in workers exposed to waste anesthetic gases - Silva, Mariane A. P. [UNESP]; Figueiredo, Drielle B. S. [UNESP]; Lara, Juliana R. [UNESP]; Paschoalinotte, Eloisa E. [UNESP]; Braz, Leandro Gobbo [UNESP]; Braz, Mariana Gobbo [UNESP] (Springer Nature, 2022)
Professionals who work in operating rooms (ORs) may be exposed daily to waste anesthetic gases (WAGs) due to the use of inhalational anesthetics. Considering the controversial findings related to genetic damage and redox status in addition to a lack of knowledge about the effect of polymorphisms in genes related to phase I and II detoxification upon occupational exposure to WAGs, this cross-sectional study is the first to jointly evaluate biomarkers of genetic instability, oxidative stress, and susceptibility genes in professionals occupationally exposed to high trace amounts of halogenated (≥ 7 ppm) and nitrous oxide (165 ppm) anesthetics in ORs and in individuals not exposed to WAGs (control group). Elevated rates of buccal micronucleus (MN) and nuclear bud (NBUD) were observed in the exposure group and in professionals exposed aged more than 30 years. Exposed males showed a higher antioxidant capacity, as determined by the ferric reducing antioxidant power (FRAP), than exposed females; exposed females had higher frequencies of MN and NBUD than nonexposed females. Genetic instability (MN) was observed in professionals with greater weekly WAG exposure, and those exposed for longer durations (years) exhibited oxidative stress (increased lipid peroxidation and decreased FRAP). Polymorphisms in metabolic genes (cytochrome P450 2E1 (CYP2E1) and glutathione S-transferases (GSTs)) did not exert an effect, except for the effects of the GSTP1 (rs1695) AG/GG polymorphism on FRAP (both groups) and GSTP1 AG/GG and GSTT1 null polymorphisms, which were associated with greater FRAP values in exposed males. Minimizing WAG exposure is necessary to reduce impacts on healthcare workers.
Keywords: Anesthetic gases; Genetic polymorphisms; Micronucleus assay; Occupational exposure; Operating room; Oxidative stress